1991
DOI: 10.1042/bj2790155
|View full text |Cite
|
Sign up to set email alerts
|

Purification and partial characterization of a pyruvate oxidoreductase from the photosynthetic bacterium Rhodospirillum rubrum grown under nitrogen-fixing conditions

Abstract: A pyruvate oxidoreductase with the capacity to support pyruvate-dependent nitrogenase activity in vitro has been purified from the photosynthetic bacterium Rhodospirillum rubrum. The enzyme requires CoA for activity and is irreversibly inactivated by oxygen. The molecular properties and Km values for the substrates have been studied. In supporting nitrogenase activity addition of ferredoxin is required. Overall the enzyme is similar to the nif-specific pyruvate: flavodoxin oxidoreductase purified from Klebsiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 34 publications
2
42
0
Order By: Relevance
“…For Rhodobactersphaeroides, it has been proposed that reductant is generated via an energized membrane (10). Pyruvate-driven nitrogenase reduction, stimulated by the addition of ferredoxins, has been observed by using crude extracts of R. rubrum (22), and a pyruvate:ferredoxin oxidoreductase has been isolated and characterized (5 …”
Section: Discussionmentioning
confidence: 99%
“…For Rhodobactersphaeroides, it has been proposed that reductant is generated via an energized membrane (10). Pyruvate-driven nitrogenase reduction, stimulated by the addition of ferredoxins, has been observed by using crude extracts of R. rubrum (22), and a pyruvate:ferredoxin oxidoreductase has been isolated and characterized (5 …”
Section: Discussionmentioning
confidence: 99%
“…2 suggest that this is also true for T. litoralis. From recent molecular analyses (32), it was concluded that the PORs in mesophilic organisms (11,30,43,57,62,63,67), most of which contain a single large subunit (14,27,32,49), originated from four ancestral genes of the type now present in the hyperthermophilic 2-ketoacid oxidoreductases (8,32,34). VOR is especially interesting in this respect because of its broad substrate specificity, suggesting that it is perhaps even more closely related than POR or KGOR to the putative ancestral oxidoreductase.…”
Section: Por and Kgor Comprise Four Different Subunits (␣␤␥␦) Withmentioning
confidence: 99%
“…A nifJ-like gene encoding a pyruvate-ferredoxin oxidoreductase has been identified (6,32). This pyruvate-ferredoxin oxidoreductase has been shown to support nitrogenase activity in vitro, linking the oxidation of pyruvate to the reduction of nitrogenase by using partially purified ferredoxin fractions (6).…”
mentioning
confidence: 99%
“…A nifJ-like gene encoding a pyruvate-ferredoxin oxidoreductase has been identified (6,32). This pyruvate-ferredoxin oxidoreductase has been shown to support nitrogenase activity in vitro, linking the oxidation of pyruvate to the reduction of nitrogenase by using partially purified ferredoxin fractions (6). Studies of a knockout mutant strain revealed no phenotype with respect to nitrogen fixation, indicating that the nifJ-like gene product is not likely to be part of the major pathway for electron transfer to nitrogenase in R. rubrum (32).…”
mentioning
confidence: 99%